Targeting strategic investment in livestock development as a vehicle for rural livelihoods - Staal, Steven J.; Poole, Elizabeth J.; Baltenweck, Isabelle; Mwacharo, Joram M.; Notenbaert, An Maria Omer; Randolph, Thomas F.; Thorpe, W.R.; Nzuma, J.; Herrero, Mario (International Livestock Research Institute, 2009)
The purpose of this report is first to provide evidence of the role of livestock in rural livelihoods in Sub-Saharan Africa and South Asia. Further, the report aims to identify opportunities for investments that build on that evidence and hold promise for improving and sustaining the livelihoods of smallholder livestock producers and their rural communities in developing countries. This analysis is presented in order to support the decision making of those public and private development investors, and policy makers, for whom improved rural livelihoods is a key objective. The report is presented in two parts. Part 1 comprises summaries of in-depth analysis of key issues central to the role of livestock and rural livelihoods, each of which brings together a wide range of available data to inform the topic. Part 2 then uses the information generated and presented in Part 1 and through a conceptual framework for guiding pro-poor livestock investment, identifies the key value chains or livestock systems and regions that are demonstrated by the evidence to offer livelihood opportunities, and some initial description of best bet types of interventions.